SELF MEDICATION INFLUENCED BY SOCIAL MEDIA: PHARMACIST’S ROLE IN THE PREVENTION TOOL - Bárbara Martins Correia, Alana; Sousa Soares, Sawanny; Laiany V. Moura, Michely (Health and Society, 2022)
Self-medication is conceptualized as the use of medication without prescription, medical or pharmaceutical advice, being a public health issue, which can cause problems such as intoxication, allergic reactions, and can lead to death. This practice has become quite common and has been propagated mainly by social media, where public people such as digital influencers and YouTubers disseminate information about their benefits achieved using drugs that can often be used even for aesthetic purposes. The cause of many current problems. The pharmacist in the field of drug misuse is extremely important, as his guidance helps in a complex way to reverse the risks of self-medication and alleviate his practice through the correct way to dispense the drugs. This study aimed to analyze the role of the pharmacist facing self-medication influenced by social media. This study is a bibliographical, integrative and qualitative review. Data collection was performed in databases in SCIELO, PubMed, CRF, JUS and ANVISA, using the keywords: self-medication, influence, social media and pharmaceutical assistance, in Portuguese and English. (Self-medication, influence, social media and pharmaceutical assistance), considering the individual and combined search for indicators. It is concluded that the implementation of the pharmacist in the health teams is necessary for the correct orientation of the proper use of drugs in order to avoid and alleviate the practice of self-medication influenced by social media.